Are public health physicians still needed in medically underserved rural areas in Korea?. Issue 19 (May 2017) - Na, Baeg Ju; Lee, Jin Yong; Kim, Hyun Joo
Abstract : Abstract: Public health physicians (PHPs) are certified physicians who are serving in a public health center or subcenter in a rural village, instead of serving in the military. However, the PHP program has recently become the subject of a profound debate, over 30 years after its adoption. In this study, we attempted to ascertain physicians' perspectives on the PHP program, including: whether the PHP policy should continue; if they agree on changing the role of PHPs in healthcare; what would be the desired role of PHPs; and what resources would be required and what possible barriers would be anticipated under the changes. We selected 88 PHPs as our study sample using quota sampling. Over 60% of respondents were in support of continuing the PHP program. They believed some remote islands and mountainous areas are still in need of public healthcare doctors. However, some of them believed that the role of PHPs should be changed to take on community health promotion, because the problem of medically underserved rural areas has almost been resolved. However, people living in rural areas are ageing and suffering from a lack of education and health information. In particular, in order to successfully transition into new roles, PHPs must be provided with continuing education and professional development programs covering their new responsibilities. It is imperative to refurbish the PHP program to meet current needs and continue its central role in public healthcare.